El incidente de la tajada de sandía, la insurrección espontánea como mecanismo de resistencia e identidad en Panamá - Güendel, Hermann (2010)
In this article I analize the spontaneous street insurrection that took place in Panama City, in 1856. This event set the ethical and political meaning for the construction of panamenian national identity.